AN ANALYSIS OF MAXIM VIOLATION IN THE LEGEND OF DRAGOON GAME - Kevin Tumimomor; Jim R. Tuna; Sarah Kamagi (Program Studi Pendidikan Bahasa Inggris, 2023)
The aim of this research was to investigate the various types of maxims that were breached in the first chapter of The Legend of Dragoon game. A descriptive qualitative approach was adopted for the study, and the data was gathered by recording statements made by characters in the game that violated the maxims. The data was obtained from both the game and its script, and notes were taken while observing and reading to identify occurrences of maxim violation. The outcomes revealed that all four types of maxims were broken by the characters in the game, with a total of 20 dialogues. The maxim of relevance was found to be the most frequently violated maxim, with seven instances, followed by the maxim of manner with six occurrences, the maxim of quality with four occurrences, and finally, the maxim of quantity in three instances